Comparison of Stress Patterns in Edentulous Mandibular Bone around Two Implant Retained, Four Implant Retained Overdenture and All-On-Four Concept. - A 3 Dimensional Finite Element Analysis (Indian Journal of Forensic Medicine & Toxicology, 2020)
Recently the use of tilted implants has been considered as a preferable option in case of atrophic edentulousarches. The tilted longer implants can be of use to ward off the important anatomical structures while alsopermitting cantilever reduction.Since the load transfer mechanism of an implant can be altered significantly by the number of implantsand its location in the edentulous ridge, the present study evaluates and compares the stress patterns in theedentulous mandibular bone around two implant retained, four implant retained over denture and all on fourconcepts under different loading conditions using finite element analysis.Purpose: The biomechanical behaviour of the ‘All-On-Four’ system was compared with that of the twoimplant-supported and four-implant supported mandibular overdenture using the three dimensional finiteelement method (FEM). Thereby evaluating the von Misses stresses induced on the implants under differentloading simulations.Materials & Method: Three dimensional models representing mandible restored with ‘All-On-Four’, twoimplant-supported and four-implant-supported prosthesis were developed in the three dimensional designsoftware and then transferred into FEM software. The models were then subjected to four different loadingsimulations (full mouth biting, canine disclusion, load on cantilever, load in the absence of cantilever). Themaximum von Mises stresses were localized and quantified for comparison.1Results: Among the three models, under all loading simulations, the maximum stress concentrations werealong the neck of theimplant. The stress levels for full mouth loading simulation was highest for twoimplant supported overdenture design and theleast for All-On-Four overdenture design. In all three designs,the least stress was when the implants were loaded in a lateraldirection. The stress levels for cantilever andnon-cantilevered designs were nearly the samefor all the simulated designs.Conclusion: When tested under differentloading simulations, the three modelsshowed similar location and distribution ofstresspatterns. Thus from the study it can beconcluded that the All-On-Four Concept is a clinically applicable treatment option for theatrophic edentulous ridges and induces least amount of stresseson the edentulous ridges. Therefore the overall longevity of theprosthesis is greatly enhanced.